A comparative study on maintenance for government and private low cost flats / Suriyani Abd Malik - Abd Malik, Suriyani (Faculty of Architecture, Planning and Surveying, 2010)
Maintenance for flat low cost housing is not new in Malaysia, as it was introduced in 1971 under New Economic Policy for Low Cost Flats. In order to enhance quality maintenance in the housing industry, the government has standardisation requirement to maintain the Low Cost Flats. The among of the objective for this research to identify and compare the maintenance body for each case study and also to identify any problem occur in maintaining those building including facilities provided. The data was collected by three method which are by literature review, questionnaire survey and observation on the maintenance for low cost flat units. The respondents for the survey covered 80 low cost housing dwellers in four (4) case study of low cost flat in Cheras area. The occupants for Low Cost Flats in Cheras were generally satisfied with quality of maintenance work and make comparative between government and private sector.